Comparative study on foreign drivers' characteristics using traffic violation and accident statistics in Japan. (July 2017) - Yoh, Kento; Okamoto, Tsutomu; Inoi, Hiroto; Doi, Kenji
Abstract: Recently the number of foreign drivers has been rapidly increasing. Hence, the driving safety measures for foreign drivers have become more essential. This study aims to identify the characteristics of foreign drivers through analyzing traffic violation and traffic accident data in Japan. Chi-square test of independence and specialization coefficient were applied, in order to understand the specific violations and accidents with high tendency with respect to the region the foreign driver hails from. Also, multi-regression analysis was utilized to reveal the relationships between traffic violations and accidents. As a result, it was revealed that sense of priority, speed, and comprehension of rules affect traffic violations. Asian drivers tend to violate the rules related to priority in the road space, while North and South Americans violate rules related to speed, and South East Asian drivers violate rules related to priority and comprehension of traffic rules and road signs. Asian drivers tend to cause crossing collision while on the other hand North and South Americans are prone to head-on collision and rear-end collision. It was concluded that driving safety measures based on drivers' characteristics with respect to region were effective. This study seeks to contribute to the improvement of traffic safety for foreigners in Japan. Highlights: Traffic violations and accidents of foreign drivers were internationally compared. Sense of priority, speed and comprehension of rules affect traffic violations. Relationships between traffic violations and accidents were statistically revealed. Effective safety measures were indicated based on drivers' characteristics by region.